2010
DOI: 10.1159/000275673
|View full text |Cite
|
Sign up to set email alerts
|

Splice Site Mutations in the P-Cadherin Gene Underlie Hypotrichosis with Juvenile Macular Dystrophy

Abstract: Background: Hypotrichosis with juvenile macular dystrophy (HJMD; OMIM 601553) is a rare autosomal recessive disorder characterized by hypotrichosis with short scalp hair and progressive macular dystrophy leading to blindness between the second and the fourth decades of life. HJMD is caused by mutations in the P-cadherin gene (CDH3), a member of the family of classical cadherins. Methods: We analyzed the DNA from members of 2 consanguineous Pakistani families with HJMD for mutations in the P-cadherin gene throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Previous mutations in CDH3 found to cause HJMD include R503H, 1 IVS2+1G→A/E504K, 2 H575R, 2 R221X, 2 981delG, 3 Y615X, 7 L168X/2112del G 9 462delT, 9 829delG, 9 IVS12‐2A→G, 11 IVS10‐1G→A, 12 IVS10‐1G→T 13 . In the present case study, we have identified a novel nonsense mutation in CDH3 in a patient with HJMD.…”
Section: Discussionmentioning
confidence: 58%
“…Previous mutations in CDH3 found to cause HJMD include R503H, 1 IVS2+1G→A/E504K, 2 H575R, 2 R221X, 2 981delG, 3 Y615X, 7 L168X/2112del G 9 462delT, 9 829delG, 9 IVS12‐2A→G, 11 IVS10‐1G→A, 12 IVS10‐1G→T 13 . In the present case study, we have identified a novel nonsense mutation in CDH3 in a patient with HJMD.…”
Section: Discussionmentioning
confidence: 58%
“…G277). In addition to the missense mutations, 4 splice-site mutations are known; these are shown in figure 3 A [Indelman et al, 2007;Jelani et al, 2009;Kamran-ul-Hassan et al, 2010;Shimomura et al, 2010]. A large number of the deletion and substitution mutations are known to cause premature termination of the protein (829delG, 462delT, L168X, R221X, 981delG, Y615X, 2112delG) [Indelman et al, 2003[Indelman et al, , 2005[Indelman et al, , 2007Kjaer et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…CDH3 mutations cause two autosomal recessive disorders, hypotrichosis with juvenile macular dystrophy (HJMD;OMIM 601553) and ectodermal dysplasia, ectrodactyly and macular dystrophy (EEM;OMIM 225280), which are associated with hair abnormalities. Dermatologically, these patients show sparse and short hair throughout life, an increased percentage of HFs in the regression (catagen) or resting stage (telogen) of the hair cycle, and abnormal hair shafts (Supplementary Figure S1a-d online; Sprecher et al, 2001;Indelman et al, 2002Indelman et al, , 2007Bergman et al, 2004;Kjaer et al, 2005;Leibu et al, 2006;Shimomura et al, 2008Shimomura et al, , 2010Jelani et al, 2009). Although this suggests that P-cadherin is required for normal hair growth, it remains unknown how P-cadherin impacts the human HFs.…”
mentioning
confidence: 99%